Death March, Second Edition - Yourdon, Edward (Pearson, 2003)
Death March Second Edition The #1 guide to surviving "doomed" projects...Fully updated and expanded, with powerful new techniques! At an alarming rate, companies continue to create death-march projects, repeatedly! What's worse is the amount of rational, intelligent people who sign up for a death-march projectsaeprojects whose schedules, estimations, budgets, and resources are so constrained or skewed that participants can hardly survive, much less succeed. In Death March, Second Edition , Ed Yourdon sheds new light on the reasons why companies spawn Death Marches and provides you with guidance to identify and survive death march projects. Yourdon covers the entire project lifecycle, systematically addressing every key issue participants face: politics, people, process, project management, and tools. No matter what your role--developer, project leader, line-of-business manager, or CxO--you'll find realistic, usable solutions. This edition's new and updated coverage includes: Creating Mission Impossible projects out of DM projects Negotiating your project's conditions: making the best of a bad situation XP, agile methods, and death march projects Time management for teams: eliminating distractions that can derail your project "Critical chain scheduling": identifying and eliminating organizational dysfunction Predicting the "straw that breaks the camel's back": lessons from system dynamics Choosing tools and methodologies most likely to work in your environment Project "flight simulators": wargaming your next project Applying triage to deliver the features that matter most When it's time to walk away This isn't a book about perfectly organized projects in "textbook" companies. It's about your project, in your company. But you won't just recognize your reality: you'll learn exactly what to do about it.
Online resource; Title from title page (viewed November 6, 2003)
Keywords: Computer software -- Development; Computer software; Development